2004
DOI: 10.1002/elps.200305784
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmotic flow in a poly(dimethylsiloxane) channel does not depend on percent curing agent

Abstract: Poly(dimethylsiloxane) (PDMS) microfluidic devices were prepared from different ratios of "curing agent" (which contains silicon hydride groups) to "base" (which contains vinyl-terminated noncross-linked PDMS), to determine the effect of this ratio on electroosmotic flow (EOF). In fabricating devices for this purpose, a novel method for permanently enclosing PDMS channels was developed. As a supplement to the microfluidic method, the inner walls of capillaries were coated with PDMS formed from varying ratios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Native PDMS with its negative surface charge supports EOF towards the cathode. 39 It can be seen that at both pH values investigated, APTES-modified PDMS microchannels supported EOF in the opposite direction to native PDMS. This is presumed to arise from the presence of net positive charge at the surface originating from the protonation of basic aminopropyl groups.…”
Section: B Reactivity Of Amine-functionalized Surface Of Aptes-modifmentioning
confidence: 91%
“…Native PDMS with its negative surface charge supports EOF towards the cathode. 39 It can be seen that at both pH values investigated, APTES-modified PDMS microchannels supported EOF in the opposite direction to native PDMS. This is presumed to arise from the presence of net positive charge at the surface originating from the protonation of basic aminopropyl groups.…”
Section: B Reactivity Of Amine-functionalized Surface Of Aptes-modifmentioning
confidence: 91%
“…However, their attenuated total reflection infrared (ATR-IR) spectroscopy experiments showed that oxygen plasma treated PDMS has large O-H stretches (which suggests the existence of silanol groups on the surface), while native PDMS does not; the absence of silanol spectroscopic features on native PDMS seems inconsistent with the hypothesis that silica filler impurities account for the surface charge. More recently, Wheeler et al [29] also found that m EO in PDMS does not depend on the relative amount of curing agent used, indicating that impurities, if important, seem insensitive to concentration.…”
Section: Impuritiesmentioning
confidence: 95%
“…The inconsistency of the data was explained by the differences in the PDMS formulations used. PDMS microfluidic devices have been prepared using different ratios of the base component (which contains vinyl-terminated noncross-linked PDMS) to the curing agent (which contains silicon hydride groups) [33]. However, EOF in these PDMS devices was found to be constant for the PDMS formed with each ratio.…”
mentioning
confidence: 99%